Pengaruh Pengelolaan Sumber Daya Manusia (SDM) dan Kepuasan Kerja terhadap Produktivitas Kerja Karyawan pada PT Nikkatsu Electric Works Kota Bandung - Yogi Suprayogi; Ripan Maldini; Mohammad Fauzi Kusumawardana (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This research aims to determine the influence of HR management on work productivity, the effect of job satisfaction on work productivity, and the influence of HR management and job satisfaction on the work productivity of employees of PT Nikkatsu Electric Works, Bandung City. This research method is quantitative. With a population of 47 people, the total number of employees is PT Nikkatsu Electric Works. The research sampling method uses a saturated sample method so that the number of samples is the same as the total population. Data analysis uses multiple linear regression analysis. The research results show that HR Management and Job Satisfaction partially and simultaneously influence work productivity, contributing to a 72.8% conclusion of the influence of human resource management (HR) and job satisfaction on team member work productivity. Keywords: HR Management, Job Satisfaction, Work Productivity